2013
DOI: 10.2991/itmr.2013.3.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of E-Health Record Systems and E-Medical Record Systems in China

Abstract: In 2005, Chinese government defined its direction to electronic health records and electronic medical records. Up to 2012, hundreds of electronic health record systems and electronic medical systems have been developed, but the systems are still in their infancy, and China is facing a variety of challenges in implementation of the systems. To overcome the challenges and achieve system benefits, recommendations are provided for implementing a national electronic health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
(9 reference statements)
0
25
0
Order By: Relevance
“…Partly in consequence, information security has not attracted significant attention from healthcare providers [33,34], although some attempts have been made to protect patient data [35][36][37][38]. Gao suggests two main reasons for the lack of motivation: (1) the Chinese traditional culture does not address the importance of personal privacy; and (2) healthcare systems in China are still in their infancy and there has not been large-scale health data exchange that can potentially trigger large amounts of privacy violations [39]. However, the implementation of healthcare information systems can hardly be successful if information privacy cannot be ensured [40].…”
Section: Incident Learning In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Partly in consequence, information security has not attracted significant attention from healthcare providers [33,34], although some attempts have been made to protect patient data [35][36][37][38]. Gao suggests two main reasons for the lack of motivation: (1) the Chinese traditional culture does not address the importance of personal privacy; and (2) healthcare systems in China are still in their infancy and there has not been large-scale health data exchange that can potentially trigger large amounts of privacy violations [39]. However, the implementation of healthcare information systems can hardly be successful if information privacy cannot be ensured [40].…”
Section: Incident Learning In Healthcarementioning
confidence: 99%
“…However, the implementation of healthcare information systems can hardly be successful if information privacy cannot be ensured [40]. There is a need to learn successful practices from international experience to improve healthcare security management systems [39].…”
Section: Incident Learning In Healthcarementioning
confidence: 99%
“…22,23 Some hospitals are investing in systems based on electronic medical records but such systems are not well integrated and the recorded data are rarely shared between hospitals or assimilated at regional level. 24 Some shortcomings in the quality of health care in China were revealed when 1086 records of medical malpractice litigation, from a third-party database, were investigated -but the sample selection method employed to create the database could not be determined. 5 Of the 504 physicians recorded in a cross-sectional survey in the Chinese city of Shenzhen, only 10 (2.0%) reported that they had been involved in medical malpractice litigation.…”
Section: Researchmentioning
confidence: 99%
“…Third, the mechanism of healthcare partnership between community health centers and tertiary hospitals (i.e., district center hospitals) has been well developed since China unveiled the national healthcare reform plan [18]. Fourth, EMR (electronic medical record) systems have been widely used by hospitals in China [19]. The carefully selected EMR can reflect the insight of the specialists, who are directly caring for a patient in practice, and thus, can provide resources for our case-based learning service to community doctors.…”
Section: Introductionmentioning
confidence: 99%